2023
DOI: 10.1371/journal.pone.0288915
|View full text |Cite
|
Sign up to set email alerts
|

A location-inventory model for the sustainable supply chain of perishable products based on pricing and replenishment decisions: A case study

Zahra Mohammadi,
Farnaz Barzinpour,
Ebrahim Teimoury

Abstract: In recent decades, changes in people’s lifestyles and occupations have led to new food consumption patterns around the world, with a notable growth in the demand for ready meals and meat products. Accordingly, the food industry has tried to transform the global food culture by promoting its more profitable products to become able to set a higher price for meat. Considering the short lifetime of products in perishable food supply chains, inventory decisions are considered crucial. In addition, the demand for pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Pan [ 17 ] established a cold chain logistics route optimization model from the perspective of low-carbon, and solved the model by using Wolf pack algorithm and ant colony algorithm. Mohammadi et al [ 18 ] developed a multi-objective mixed-integer non-linear programming model for a four-level sustainable supply chain of a perishable product with price-dependent demand and deterioration rates. In addition, some scholars have carried out extended studies on the influence of factors such as facility capacity limitation [ 19 ], influence of multiple vehicle types [ 20 ], and inventory cost [ 21 , 22 ] on LRP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pan [ 17 ] established a cold chain logistics route optimization model from the perspective of low-carbon, and solved the model by using Wolf pack algorithm and ant colony algorithm. Mohammadi et al [ 18 ] developed a multi-objective mixed-integer non-linear programming model for a four-level sustainable supply chain of a perishable product with price-dependent demand and deterioration rates. In addition, some scholars have carried out extended studies on the influence of factors such as facility capacity limitation [ 19 ], influence of multiple vehicle types [ 20 ], and inventory cost [ 21 , 22 ] on LRP.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was found that whether the supply chain carried out green product R&D would be affected by the competitive supply chain selection strategy and the cost of green product R&D. Zhang et al [ 52 ] established a mixed integer programming model to study the optimal design of sustainable supply chain network, and put forward a chaotic particle-ant colony algorithm to solve multi-objective functions. Mohammadi et al [ 53 ] established a multi-objective mixed integer nonlinear programming model for the sustainable supply chain of perishable products with price-dependent demand and deterioration rate, determined the optimal pricing strategy and cycle length, and achieved profit maximization and specific social goals. Fu et al [ 54 ] discussed the influence of non-subsidy policy, fixed subsidy policy and agricultural risk coverage (ARC) subsidy policy on government costs, farmers and enterprise profits.…”
Section: Literature Reviewmentioning
confidence: 99%